1998
DOI: 10.1021/bp980085w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Redox Potential with State Variables in Cultures under Controlled Dissolved Oxygen Concentration and pH

Abstract: In batch cultures for L-ornithine production in which dissolved oxygen concentration and pH were closely controlled, time changes of redox potential were observed in connection with the profiles of cell, glucose, and ornithine concentrations. It was found that the redox potential profile had four different phases reflecting the physiological state of the culture and that it was closely related to cell concentration change. Effects of glucose and ornithine on the redox potential were identified in a separate se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, disruption of competing pathways was also effective to improve the polymer production [ 17 ]. On the other hand, optimization of fermentation parameters such as pH, aeration rate etc, was useful to achieve high cell density and production per unit time [ 18 , 19 ]. These strategies for the metabolic and fermentation engineering of PHA producers were implemented either individually or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, disruption of competing pathways was also effective to improve the polymer production [ 17 ]. On the other hand, optimization of fermentation parameters such as pH, aeration rate etc, was useful to achieve high cell density and production per unit time [ 18 , 19 ]. These strategies for the metabolic and fermentation engineering of PHA producers were implemented either individually or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [63] observed correlations between redox potential (Eh) and glucose, cell and ornithine concentrations and proposed that these parameters could be applied for online measurements of Brevibacterium ketoglutamicum growth parameters and metabolite biosynthesis. Such indicators could also be considered for monitoring hairy roots growth.…”
mentioning
confidence: 99%